FIGURE 3 in The lionfishes: Comparative development of Pterois volitans, Dendrochirus barberi, and D. hemprichi (Scorpaeniformes: Scorpaenidae: Pteroinae) and discrimination of their early life stages from non-pteroine scorpaenid genera in the Western North Atlantic - Ditty, James G.; Malca, Estrella; Vásquez-Yeomans, Lourdes (Zenodo, 2024)
FIGURE 3. Cranial and opercular spination in Pterois volitans larvae. A. 3.6 mm; B. 8.0 mm; C. 9.3 mm (pelvic fins not to scale). All lengths in mm standard length (SL) post-preservation. Published as part of Ditty, James G., Malca, Estrella & Vásquez-Yeomans, Lourdes, 2024, The lionfishes: Comparative development of Pterois volitans, Dendrochirus barberi, and D. hemprichi (Scorpaeniformes: Scorpaenidae: Pteroinae) and discrimination of their early life stages from non-pteroine scorpaenid genera in the Western North Atlantic, pp. 1-41 in Zootaxa 5446 (1) on page 13, DOI:10.11646/zootaxa.5446.1.1, http://zenodo.org/record/11084543